Estudio técnico del autoabastecimiento eléctrico para una torre autosoportada de control de tráfico y vigilancia marítima a partir de un sistema de energía solar fotovoltaico - Álvarez Jiménez, Jehider Yair (Universidad Antonio Nariño, 2021)
The main objective of this project is to carry out a technical study on the electrical selfsupply for a tower of the traffic control and maritime surveillance system located on Soldado Island, in the department of Valle del Cauca from a photovoltaic solar energy system, This in order to provide the National Navy and the General Maritime Directorate (DIMAR) with a tool that allows them to determine the viability of replacing or supporting the current electricity generation model that works through internal combustion plants, with an energy system renewable capable of supplying the energy required to supply the self-supporting tower.